Harnessing speckle for a sub-femtometre resolved broadband wavemeter and laser stabilization - Nikolaus Klaus Metzger (Nature Portfolio, 2017)
The complex speckle pattern produced by coherent multiple scattering contains information about the incident light field, which has recently been used for imaging. Metzgeret al. use speckle to construct a wavemeter with sub-femtometre resolution which is subsequently used for laser stabilization.